Aberrant Phenotype in Iranian Patients with Acute Myeloid Leukemia - Mehdi Jahedi; Karim Shamsasenjan; Zohreh Sanaat; Mohammad Reza Aliparasti; Shohreh Almasi; Mozhdeh Mohamadian; Babak Nejati; Amir Kamalifar; Ali Akbar Movassaghpour (Tabriz University of Medical Sciences, 2014)
Purpose: The aim of this study was to evaluate the incidence of aberrant phenotypes and possible prognostic value in peripheral and bone marrow blood mononuclear cells of Iranian patients with AML. Methods: 56 cases of de novo AML (2010-2012) diagnosed by using an acute panel of monoclonal antibodies by multiparametric flowcytometry. Immunophenotyping was done on fresh bone marrow aspirate and/or peripheral blood samples using the acute panel of MoAbs is stained with Phycoerythrin (PE) /fluorescein isothiocyanate (FITC), Allophycocyanin (APC) and Peridinin-chlorophyll protein complex (perCP). We investigated Co-expression of lymphoid-associated markers CD2, CD3, CD7, CD 10, CD19, CD20 and CD22 in myeloblasts. Results: Out of the 56 cases, 32 (57.1%) showed AP. CD7 was positive in 72.7% of cases in M1 and 28.5% in M2 but M3 and M4 cases lacked this marker. We detected CD2 in 58.35 of M1cases, 21.40% of M2 cases, 33.3 of M3 and 20% of M5; but M4 patients lacked this marker. The CBC analysis demonstrated a wide range of haemoglobin concentration, Platelet and WBC count which varied from normal to anaemia, thrombocytopenia to thrombocytosis and leukopenia to hyper leukocytosis. Conclusions: Our findings showed that CD7 and CD2 were the most common aberrant marker in Iranian patients with AML. However, we are not find any significant correlation between aberrant phenotype changing and MRD in our population. Taken together, this findings help to provide new insights in to the investigation of other aberrant phenotypes that may play roles in diagnosis and therapeutic of AML.